DIFFERENTIATION IN MORPHOLOGICAL CHARACTERISTICS, BASIC-MOTOR AND FUNCTIONAL ABILITIES OF HIGH SCHOOL STUDENTS - Adnan Bukvić,; Dževad Džibrić,; Admir Hadžikadunić,; Rijad Novaković, (Sport Scientific And Practical Aspects, 2025)
One of the main accompanying parts of the growth and development of students is their systematic monitoring of certain anthropological dimensions. This research, which is of a transversal character, had a goal to determine differences in morphological characteristics, basic-motor and functional abilities between students from different grades of high school. The population from which the sample of 349 respondents was taken is defined as the population of the first, second, third and fourth grades students from Zavidovići high schools, male, 15 to 18 years old ± 6 months. The sample of variables consisted of a set of 20 (twenty) tests for the assessment of anthropological dimensions, as follows: morphological characteristics (4 variables), basic-motor abilities (15 variables) and functional abilities (1 variable). A univariate analysis of variance with multiple comparisons was used to determine the differences in the study spaces between students of different grades of high school, with the applied Bonferroni post-hoc test. The obtained results showed that there are statistically significant differences in three of the four morphological variables (body height, body weight and body mass index), in eight of fifteen motor abilities (ball rolling with non- dominant hand, direction switch on training ground, side stepping, figure eight with crouching, running transmission, forward bend on the bench, standing long jump and sit-ups) and one functional variable (1000 m run) between the treated groups at the significance level (p≤0.05). The obtained results can be subject to a critical analysis of the physical and health education teaching process in order to more efficiently organize and rationalize the teaching of physical and health education. This data may show certain shortcomings of year-round application of funds as part of the realization of the high school plan and program